Nota sobre los brezales de la provincia de Burgos - Tarazona, Teresa; Zaldívar, Pilar (Lazaroa, 1985)
larazona, 1. & Zaldívar, P.: Notes un beathland nf provínce of Burgos. Wc have studied o this paper <he heathlands in the Cántahro-Euska[dún. CastellanoCantábrico and Ibérico-Soriano ehorological sectors of Burgos. Twu new subasociations are described Dai,eeria- lil/retum ga/// erir-etesuro letra/iris- and Dabaecie- <Iliecturo gal// ardes-íapby-leíun~ rras.sífo//ae. A new provisional cominunitie of Gen/ide//a jr/dentata and Arrtt:,stapiules -rass/Ji1/ce is alse described.